La Innovación Curricular Educativa y sus efectos en el mejoramiento de la calidad ofertada en la Unidad Educativa Victoria Macías de Acuña del cantón Milagro - Macías Arroyo, Franklin (2015)
This research is a contribution to education and collecting daily shortcomings in the learning processes involved with teachers, students, parents and managers. Based on the on-site investigation on the application of curriculum innovation implemented by the present national government, we check with teachers problems, hardships they face in exercising their work in each classroom. From the "milagreña educational tradition" we performed a look inward and determine whether the curriculum innovation is effective in improving the quality offered by the school of basic education Acuna Victoria Macias Canton Milagro. We found that some improvement could be implemented that are centralized in the administrative steps that can only exercise educational districts. We aim to strengthen the quality of education with the implementation of our proposal a program that allows access to members of the educational community, and all have the same common interest to improve learning processes.